Strategi Guru Pendidikan Agama Islam Dalam Membelajarkan Pendidikan Seks Di SMP Swasta Budisatrya Medan - Nur Latifah Lubis; Abdul Fattah Nasution; Juli Julaiha Pulungan (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study, titled "Islamic Religious Education Teachers' Strategies in Teaching Sex Education at SMP Swasta Budisatrya Medan," is based on observations that many students at SMP Swasta Budisatrya Medan face challenges in understanding sex education content that is not explicitly stated in the curriculum. This research aims to analyze the strategies used by Islamic Religious Education (PAI) teachers in delivering sex education to students. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation at SMP Swasta Budisatrya Medan in the 2023/2024 academic year. Primary data sources are derived from observations and interviews, while secondary data sources are from school documents and archives. Data analysis techniques include data reduction, data presentation, and conclusion/verification. The results show that the strategies used by PAI teachers in teaching sex education include integrating relevant content into appropriate lessons, using lecture and discussion methods, and developing materials based on the teachers' personal experiences. These strategies are effective in enhancing students' understanding of sex education, despite challenges such as the lack of specific references and supporting teaching media. It is recommended that teachers continue to develop culturally and socially sensitive teaching strategies to address challenges in sex education.